2011
DOI: 10.1128/jvi.02260-10
|View full text |Cite
|
Sign up to set email alerts
|

Factors Supporting Intrathecal Humoral Responses following Viral Encephalomyelitis

Abstract: Central nervous system (CNS) infections and autoimmune inflammatory disorders are often associated with retention of antibody-secreting cells (ASC). Although beneficial or detrimental contributions of ASC to CNS diseases remain to be defined, virus-specific ASC are crucial in controlling persistent CNS infection following coronavirus-induced encephalomyelitis. This report characterizes expression kinetics of factors associated with ASC homing, differentiation, and survival in the spinal cord, the prominent sit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
79
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
1

Relationship

4
3

Authors

Journals

citations
Cited by 46 publications
(86 citation statements)
references
References 77 publications
(110 reference statements)
6
79
1
Order By: Relevance
“…The expression of CXCL13 and CXCL12 is essential for follicle formation in the CNS (22,23). CXCL13 mRNA was not elevated in the brains of JHMV-infected mice (48). In response to SINV, CXCL13 and CCL19 mRNAs were induced in the brain, but CXCR5 ϩ and CCR7 ϩ B cells did not appear to be infiltrating the brain, and other investigators have shown that CXCL13 Ϫ/Ϫ mice infected with SINV have normal B-cell infiltration and virus clearance (51).…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The expression of CXCL13 and CXCL12 is essential for follicle formation in the CNS (22,23). CXCL13 mRNA was not elevated in the brains of JHMV-infected mice (48). In response to SINV, CXCL13 and CCL19 mRNAs were induced in the brain, but CXCR5 ϩ and CCR7 ϩ B cells did not appear to be infiltrating the brain, and other investigators have shown that CXCL13 Ϫ/Ϫ mice infected with SINV have normal B-cell infiltration and virus clearance (51).…”
Section: Discussionmentioning
confidence: 98%
“…Astrocytes in the CNS constitutively produce BAFF, and microglial cells secrete BAFF in vitro (24,49). In JHMV infection, the long-term maintenance of ASCs in the CNS after clearance of infectious virus and during persistence of viral RNA in glial cells coincides with astrocyte production of BAFF mRNA (16,48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To ascertain that CD19 deficiency affected overall ASC CNS migration independent of specificity, we monitored accumulation of ASC via expression of mRNAs encoding IgG and IgM heavy chains, which are highly expressed in ASC compared to non-Absecreting B cells (8). Both brains and spinal cords of infected WT mice exhibited a significant increase in IgG heavy chain mRNA by 14 days p.i., which was further elevated at days 21 through 28 p.i.…”
Section: Cd19-dependent Humoral Immunity To Cns Viral Infectionmentioning
confidence: 99%
“…Following CNS infection with a glial-tropic sublethal variant of mouse hepatitis virus (MHV), designated JHMV-v2.2-1, both T and B cell priming occurs in draining cervical lymph nodes (CLN) (5)(6)(7). While virus-specific CD4 and CD8 T cells are essential to clear infectious virus, virus-specific antibody (Ab)-secreting cells (ASC) and sustained neutralizing IgG Ab are required for long-term control of persisting virus, which is detectable only by the ongoing presence of low levels of viral RNA (5,8,9). Virus-specific ASC in CLN are CD4 dependent (10) and reach peak frequencies at ϳ14 days postinfection (p.i.)…”
mentioning
confidence: 99%